Studies on Line×Tester Analysis in Sesame (Sesamum indicum L.) - Amarnath, T.; Ram, S. Ranjith Raja; Gogulakrishnan, J.; Narayanan, R. (International Journal of Bio-resource and Stress Management, 2019)
The present investigation was carried out in sesame involving 7 lines and 3 testers to identify the nature of gene action, combining ability and heterosis in association with yield and its component traits in sesame during December 2017 –March 2019. The parents were mated in the Line×Tester method. The variance due to SCA was higher than the corresponding variance due to GCA for all the characters indicating the preponderance of non-additive gene action. Among the lines ACM 14- 007 SI-2 and GT 10 and among the tester TMV 7 and TMV 5 exhibited high and significant per se performance for seed yield and its component traits. The gca effects of the lines indicated that the line GT 10 was positive and maximum significant for the yield attributing characters. The hybrids ACM 14-007 SI-2×TMV 5 and GT 10×TMV 7 recorded high per se performance with significant sca effects for seed yield per plant its component traits. Based on standard heterosis, the cross combinations GT 10×TMV 7, ACM 14-007 SI-2×TMV 5 and GT 10×TMV 5 possessed significant high standard heterosis for seed yield per plant and its associated traits. The hybrids GT 10× TMV 7, ACM 14-007 SI-2×TMV 5 and GT 10×TMV 5 were rated as the best since it possessed desirable performance based on per se, sca effects and standard heterosis for most of the yield attributing characters and so these hybrids could be exploited for further crop improvement.